2019
DOI: 10.1186/s40425-019-0756-0
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide treatment for microscopic colitis from immune checkpoint inhibitors

Abstract: BackgroundImmune checkpoint inhibitors (CPIs) are effective against a variety of malignancies but can be limited by inflammatory toxicities such as enterocolitis. Enterocolitis is typically treated with systemically active glucocorticoids. Endoscopy can stratify patients by the severity of mucosal inflammation, including identifying patients with colitis in the absence of visible mucosal changes: microscopic colitis. Whether patients with CPI microscopic colitis could be managed differently from colitis with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 30 publications
0
57
0
Order By: Relevance
“…In a single center study of 117 patients treated with ICIs who had diarrhea, about one third required no treatment, corticosteroids, or corticosteroids plus infliximab (a tumor necrosis factor (TNF) inhibitor) 59. A randomized controlled trial showed that prophylactic budesonide was not effective against anti-CTLA-4 induced colitis,60 but it is commonly used to treat ICI-associated microscopic colitis 61. Infliximab has been associated with a shorter time to symptom resolution than corticosteroids alone,62 and vedolizumab (an antibody to α 4 β 7 integrin), has also been used as a steroid sparing agent 63.…”
Section: Clinical Presentation Of Checkpoint Inhibitor Associated Autmentioning
confidence: 99%
“…In a single center study of 117 patients treated with ICIs who had diarrhea, about one third required no treatment, corticosteroids, or corticosteroids plus infliximab (a tumor necrosis factor (TNF) inhibitor) 59. A randomized controlled trial showed that prophylactic budesonide was not effective against anti-CTLA-4 induced colitis,60 but it is commonly used to treat ICI-associated microscopic colitis 61. Infliximab has been associated with a shorter time to symptom resolution than corticosteroids alone,62 and vedolizumab (an antibody to α 4 β 7 integrin), has also been used as a steroid sparing agent 63.…”
Section: Clinical Presentation Of Checkpoint Inhibitor Associated Autmentioning
confidence: 99%
“…Although prophylactic budesonide, was not effective in preventing ipilimumab-induced diarrhoea in a phase 2 randomised placebo-controlled trial, 49 our study highlights the potential for budesonide as a primary therapeutic strategy in checkpoint inhibitor induced-enterocolitis. Eight studies report the use of budesonide, 10,14,16,27,29,30,33,37 although few describe the clinical outcomes related to its ad- Other studies report a few cases where budesonide was successfully used as the primary corticosteroid. 27,29 In line with this, a small case series (n = 2) also demonstrated that Infliximab has an established role as second-line therapy in corticosteroid refractory cases, or some instances of corticosteroid relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we observed a significant degree of heterogeneity between studies, which may be partly explained by differences in their inclusion criteria. For example, many studies included patients with any gastrointestinal symptom, 14,22,25,27,35,37,41,[60][61][62] while others were more stringent and only included patients exhibiting at least CTCAE grade 2 40,63,64 or 3 23,34 diarrhoea, endoscopic and/or histological evidence of inflammation, 16,33,42,44,[65][66][67] patients requiring corticosteroids 24,30 or having some response to immunosuppressive therapy. 68 Moreover, there was marked variation between studies Finally, in the subgroup analysis we included some studies where not all the study group belonged to the covariate being analysed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although budesonide has not been proven effective for the prevention of enterocolitis from treatment with ipilimumab, limited data have suggested that it can control symptoms and prolong the duration of immunotherapy. 13,14 Corticosteroid enemas can also alleviate symptoms of urgency and tenesmus in patients with rectosigmoid inflammation. In patients who fail to improve and those with grade 3 colitis, transition to biologic agents (eg, TNF-α inhibitor infliximab or anti-integrin vedolizumab) rather than an initial trial of high-dose glucocorticoids (prednisone at a dose of 1-2 mg/kg) may be considered.…”
Section: How Should Patients With Suspected Ici Toxicity Be Evaluatedmentioning
confidence: 99%